HOTAIR and its surrogate DNA methylation signature indicate carboplatin resistance in ovarian cancer. Issue 1 (December 2015) - Teschendorff, Andrew; Lee, Shih-Han; Jones, Allison; Fiegl, Heidi; Kalwa, Marie; Wagner, Wolfgang; Chindera, Kantaraja; Evans, Iona; Dubeau, Louis; Orjalo, Arturo; Horlings, Hugo; Niederreiter, Lukas; et al.
Abstract Background Understanding carboplatin resistance in ovarian cancer is critical for the improvement of patients' lives. Multipotent mesenchymal stem cells or an aggravated epithelial to mesenchymal transition phenotype of a cancer are integrally involved in pathways conferring chemo-resistance. Long non-coding RNAHOTAIR (HOX transcript antisense intergenic RNA) is involved in mesenchymal stem cell fate and cancer biology. Methods We analyzedHOTAIR expression and associated surrogate DNA methylation (DNAme) in 134 primary ovarian cancer cases (63 received carboplatin, 55 received cisplatin and 16 no chemotherapy). We validated our findings byHOTAIR expression and DNAme analysis in a multicentre setting of five additional sets, encompassing 946 ovarian cancers. Chemo-sensitivity has been assessed in cell culture experiments. Results HOTAIR expression was significantly associated with poor survival in carboplatin-treated patients with adjusted hazard ratios for death of 3.64 (95 % confidence interval [CI] 1.78–7.42;P  < 0.001) in the discovery and 1.63 (95 % CI 1.04–2.56;P  = 0.032) in the validation set. This effect was not seen in patients who did not receive carboplatin (0.97 [95 % CI 0.52–1.80;P  = 0.932]).HOTAIR expression or its surrogate DNAme signature predicted poor outcome in all additional sets of carboplatin-treated ovarian cancer patients whileHOTAIR expressors responded preferentially to cisplatin (multivariate interactionP  = 0.008). Conclusions Non-coding RNAHOTAIR or its more stable DNAme surrogate may indicate the presence of a subset of cells which confer resistance to carboplatin and can serve as (1) a marker to personalise treatment and (2) a novel target to overcome carboplatin resistance.